The effect of creative thinking exercises on direction perception and memory (visual-motor) in handball players under the age of 12 (Journal of Humanities and Social Sciences Research, 2026)
This study aims to identify the effect of creative thinking exercises on the development of directional perception and memory in handball players under the age of twelve. The researcher used an experimental approach with a control group and an experimental group. The research sample included several players who were deliberately selected from handball players. The experimental group underwent a training program that included creative thinking exercises designed to suit their age group. Meanwhile, the control group continued with the traditional training program. Tests of direction perception and memorisation were applied before and after the implementation of the training program. Statistical methods were used to process the results, and the results showed significant differences in favour of the experimental group in the variables of perception of direction and recall. This indicates the effectiveness of creative thinking exercises in the development of cognitive and cognitive abilities of handball players. The researcher concluded that the introduction of creative thinking exercises within the training programs contributes positively to improving spatial perception and memory, which is reflected in the skill performance of young players. The research recommends the adoption of these exercises in training young age groups and conducting similar studies on other psychological and skill variables, and in various sports games, and the need to pay attention to activating the role of creative thinking exercises in improving motor skills in general, and contributes to improving mental skills in particular.